Penguatan Ibadah Shalat Berbasis Partisipatif di Desa Gendro Kecamatan Tutur Kabupaten Pasuruan Melalui Kolaborasi Pengabdi Masyarakat, Muslimat dan Fatayat - Mukarromah Mukarromah (Universitas Islam Internasional Darullughah Wadda'wah, 2026)
This study describes a participatory community service activity aimed at strengthening the understanding and practice of prayer in Gendro Village, Tutur District, Pasuruan Regency through collaboration between community service workers, Muslimat, and Fatayat. This activity was motivated by the still diverse levels of religious understanding of the community, including converts, so that a simple, applicable, and sustainable coaching approach was needed. The method used was Participatory Action Research (PAR) which actively involved the community in all stages of the activity, starting from observation, material presentation, prayer practice, question and answer, monitoring, to evaluation and reflection. The results of the activity showed a significant increase in the understanding of the pillars, readings, and movements of prayer, as well as increased skills in practicing worship in a more orderly and according to guidance. In addition, there was also a strengthening of spiritual awareness and motivation for worship in the community, reflected in increased participation in religious activities at the mosque and the Islamic study group. Collaboration with Muslimat and Fatayat has proven effective as a community-based da'wah agent that is able to reach the community in a closer and more humane manner. Overall, this activity has a positive impact in forming a society that is more religious, independent in worship, and has a culture of sustainable religious development.